Psychological Violence at Work: Problems in Applying the Law in Lithuania - Leščinskaitė Aistė (Baltic Journal of Law & Politics)
The recent Lithuanian Law of Labor Code of 28 July 20221 introduced into Lithuanian Labor Code the concept of “psychological violence.” The definitions of psychological violence under this law adopt quite a broad conception of the notion of psychological violence. The legislator has defined the scope where psychological violence is prohibited, as well as new ground for terminations of employment contract, and use of psychological violence. The recent amendments to the Labor Code also impose numerous obligations on employers to prevent psychological violence at work, which, together with the recommendations of the State Labor Inspectorate, have caused confusion not only in companies, institutions, and organizations, but also in the lives of their managers. The limited case law after the change in the legal framework shows that the legal framework is not working as it should and is not adequately interpreted to prevent psychological violence, and therefore deserves criticism.